Attitudes towards attractive and credible celebrities in advertisements - De la Rey van der Waldt; N de Beer N de Beer; N du Plessis N du Plessis (Communicare, 2022)
The saying, beauty is in the eye of the beholder, is relevant in the use of attractive and credible celebrities in advertisements. A celebrity endorser is seen as a model who enjoys recognition from the public and who can be seen as an ubiquitous feature of marketing today. The use of celebrity endorsers is a fairly common practice in many organisations in supporting their corporate or brand image. This article focuses on both the attractiveness and also the credibility of celebrities in advertisements. It is anticipated that attractive celebrities and credible celebrities could influence attitudes positively, and that this will eventually lead to the purchasing of the advertised products and services. O’Mahony and Meenaghan’s (1997/1998) Perceptions of Celebrity Endorsements Scale was used to measure the overall attitudes of students on celebrity endorsements. Separate sets of items were developed to measure attractive and credible celebrities separately. The internal consistency reliability of these measurement scales reflected high scores (α > 0.70) on all items. In general, the respondents positively perceived celebrity endorsements. However, the overall rating of respondents in respect of an attractive celebrity in an advertisement was decidedly more unfavourable. Results also showed attitudes towards credible celebrity endorsements to be neither positive nor negative